Men’s Reflections on Their Experiences of Gender-Based Violence - Sinacore, Ada L. (Journal of interpersonal violence, 2021)
Using Multicultural and Gender Case Conceptualization (MGCC) epistemology, the aim of this phenomenological study was to explore adult male victims’ perceptions of gender and reflections on their experiences of gender-based violence (GBV). Data were analyzed using interpretative phenomenological analysis (IPA). Results indicated that, regardless of sexual orientation, participants experienced verbal and physical abuse due to their feminine gender expression, beginning in primary school and continuing through university and into the workplace. To reduce victimization, the men developed a range of strategies, such as policing their gender and avoiding social situations. The experiences of violence affected the participants’ social relationships, choice of occupation, self-esteem, and ability to trust. However, after entering university, heterosexual, gay, and bisexual participants interpreted their experiences differently, whereby heterosexual participants linked the abuse to gender, and gay and bisexual participants viewed it as homophobia. As well, gay and bisexual participants found respite in the gay and bisexual communities, while heterosexual participants remained silent, isolated, and afraid to discuss their experiences. Implications for future research are discussed.